(untitled) (Medico Legal Update, 2021)
Forensic examination, as part of the criminal process, is a complex activity in which the diagnostic moment is abnormally integrated, as the diagnosis is not intended for treatment or cure. It is understandable that the influence exerted by psychiatric examination on court decisions (it is mostly about psychiatry in general), cannot be separated from the historical relationship between psychiatry and law. In countries where the assessment of irresponsibility is based on a psychopathological-normative method, it is necessary not only to recognize the mental disorder, but also to assess how this disorder interacts psychologically in compromising the ability to understand actions and desire the advent of consequences. Reflecting on the above arguments, this paper focuses on the importance of forensic psychiatry and psychiatric examination in criminal proceedings as a legal and medical study, as well as identifying critical aspects of the inseparable relationship between psychiatry and law, until the moment when the judge will decide whether the mental disorder under the Criminal Code prevented the perpetrator from understanding the act committed, as well as whether or not he wished the consequences that came from this act.